Role of Sub Section For The Development of Criminal Investigation Bureau’s Head of Operation In The Criminal Action Process According to the Law of Regulation - Agung Joko Haryono (Airlangga Development Journal, 2020)
This research was conducted to analyze the effectiveness and efficiency of the investigation oversight process carried out by Criminal Investigation Bureau’s Head and the efforts that made by the National Police leadership in order to increase the effectiveness of criminal Investigation. This type of research in writing this thesis is analytical descriptive research in which the primary data collection method is through interviews. The results showed that the effectiveness and efficiency of the criminal investigation investigation process carried out by Criminal Investigation Bureau’s Head Gresik Polresik, which is still not optimal, because in the supervision process found deficiencies, namely at the examination stage of the administrative investigation investigation and the submits SP2HP which is not all cases are given Notification of Progress of Investigation.